Економічні засади соціально-поведінкової діяльності сімейних форм аграрного виробництва - Трусова, Наталя Вікторівна; Болтянська, Лариса Олексіївна; Trusova, Natalia; Boltianska, Larysa (Мелітополь : 2022, 2022)
UA: У статті розглядається методичні положення до оцінки соціально-поведінкової діяльності сімейних форм аграрного виробництва та особливості їх соціальної відповідальності при виконанні виробничого процесу в оточуючому економічному середовищі. Обґрунтовано, що траєкторія економічної стабільності сімейних форм аграрного виробництва із соціальною свідомістю розвитку є процесом небезперервної дії, а послідовним і цілеспрямованим проектом з певним економічним результатом, обмеженим у часі та ресурсах. Визначено орієнтири та стандартизовані норми континууму «соціально-поведінкова мобільність – економічна стабільність» сімейних форм аграрного виробництва із інтерпретованими ознаками активізації економічного розвитку за шкалою благополуччя. EN: The article considers the methodological provisions for assessing the socio and behavioral activities of family forms of agricultural production and the features of their social responsibility in the production process in the surrounding economic environment. It is substantiated that the trajectory of economic stability of family forms of agricultural production with social consciousness of development is a process of non-permanent action, and a consistent and purposeful project with a certain economic result, limited in time and resources. Guidelines and standardized norms of the continuum "socio and behavioral mobility – economic stability" of family forms of agricultural production with interpreted signs of intensification of economic development on the scale of well-being are determined. It is proved that the economic component in the social and behavioral activities of family forms of agricultural production provides a trajectory of stable development in the agro-food market. It is determined that the distribution of economic development projects in the socio and behavioral activities of family forms of agricultural production allows to specify their goals, increase the accuracy of plans and forecasts. Social trust becomes a certain basis for understanding social relations and responsibility for the production process of family forms of agricultural production. The specific features of the influence of the economic environment on social and behavioral activities and the trajectory of economic stability of family forms of agricultural production are substantiated. The components of the integration process of economic development and stable social behavior of members of the family form of agricultural production are determined, taking into account the peculiarities of their business partnership in the agro-food market. Quantitative and qualitative signs of measuring the level of social and behavioral mobility of family forms of agricultural production in the period of interruption of economic development have been established.
Economic foundations of socio-behavior activity of family forms of agricultural production
Keywords: сімейні форми; аграрне виробництво; соціальна відповідальність; економічний розвиток; економічне середовище; family forms; agricultural production; social responsibility; economic development; economic environment